2010
DOI: 10.1186/1471-2164-11-371
|View full text |Cite
|
Sign up to set email alerts
|

Comparative mitogenomics of Braconidae (Insecta: Hymenoptera) and the phylogenetic utility of mitochondrial genomes with special reference to Holometabolous insects

Abstract: BackgroundAnimal mitochondrial genomes are potential models for molecular evolution and markers for phylogenetic and population studies. Previous research has shown interesting features in hymenopteran mitochondrial genomes. Here, we conducted a comparative study of mitochondrial genomes of the family Braconidae, one of the largest families of Hymenoptera, and assessed the utility of mitochondrial genomic data for phylogenetic inference at three different hierarchical levels, i.e., Braconidae, Hymenoptera, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
121
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(140 citation statements)
references
References 87 publications
(122 reference statements)
17
121
1
1
Order By: Relevance
“…For example, the monophyly of the Proctotrupomorpha (sensu Rasnitsyn 1988) is well supported by recent studies, but the relationships among the proctotrupomorph families are still controversial (Dowton and Austin 2001;Rasnitsyn and Zhang 2010;Heraty et al 2011). Several analyses have demonstrated that the whole mt genome is a useful tool to resolve hymenopteran evolutionary relationships (Castro and Dowton 2007;Cameron et al 2008;Dowton et al 2009a;Wei et al 2010a). To date, 18 complete mt genomes and 15 nearly complete mt genomes have been successfully sequenced in the Hymenoptera, with 18 taxa added in the last 3 years.…”
Section: Introductionmentioning
confidence: 84%
“…For example, the monophyly of the Proctotrupomorpha (sensu Rasnitsyn 1988) is well supported by recent studies, but the relationships among the proctotrupomorph families are still controversial (Dowton and Austin 2001;Rasnitsyn and Zhang 2010;Heraty et al 2011). Several analyses have demonstrated that the whole mt genome is a useful tool to resolve hymenopteran evolutionary relationships (Castro and Dowton 2007;Cameron et al 2008;Dowton et al 2009a;Wei et al 2010a). To date, 18 complete mt genomes and 15 nearly complete mt genomes have been successfully sequenced in the Hymenoptera, with 18 taxa added in the last 3 years.…”
Section: Introductionmentioning
confidence: 84%
“…However, we have managed to obtain partial ends of the A + T-rich region in C. pygmeus after application of several approaches. Similar cases have been reported in insect mitogenomes as a frequently encountered problem Castro and Dowton, 2005;Castro et al, 2006;Mao et al, 2014;Wei et al, 2010b). The partial sequenced A + T-rich region and two tRNAs (trnI, trnQ incomplete for C. sareptanus) were therefore excluded from all subsequent analyses, but included in GenBank database.…”
Section: Architecture and Nucleotide Composition Of Cephus Mitogenomesmentioning
confidence: 90%
“…The rrnS secondary structure is predicted for the first time in sawflies and includes 30 helices like most known hymenopteran species (Gillespie et al, 2006;Wei et al, 2009;Wu et al, 2014), but an exception was reported for braconid species (Wei et al, 2010b) (Fig. 4).…”
Section: Ribosomal Rna Genesmentioning
confidence: 93%
“…The A + T-rich region had been reported to possess some essential elements involved in the initiation of replication and transcription process (Goddard and Wolstenholme, 1980;Zhang and Hewitt, 1997;Zhang et al, 1995;Wei et al, 2010aWei et al, , 2010b. Zhang and Hewitt (Zhang and Hewitt, 1997) reported five pertinent structure elements: (1) a poly-T stretch, which may be associated with the control of transcription and replication; (2) a [TA(A)] n like stretch following the poly-T stretch; (3) a highly conserved stem-and-loop structure, which may be involved in the replication; (4) a highly conserved flanking sequence of the stem and loop structure with a 5′ consensus of 'TATA' and a 3′ consensus of 'G(A) n T'; (5) a G + A-rich sequence block located downstream of the secondary structure.…”
Section: A + T-rich Regionmentioning
confidence: 99%
“…It usually contains a remarkably conserved set of 37 genes including 22 encoding tRNAs, 2 encoding rRNAs (lrRNA and srRNA), and 13 encoding proteins that are involved in electron transport and oxidative phosphorylation (Wolstenholme, 1992;Boore, 1999). The mitochondrial genome is highly economized with few sections of noncoding DNA, intergenic regions, or repetitive sequences (Harrison, 1989;Lunt et al, 1998aLunt et al, , 1998b, except for the A + T-rich region (also called control region) which is the most variable region in both A + T content and length of mtDNA due to the insertions/deletions of nucleotides, variation in copy numbers of sequences repeated in tandem and extensive length variation of a variable domain (Zhang et al, 1995;Rondan Duenas et al, 2002;Wei et al, 2010aWei et al, , 2010b. Additionally, the control region harbors some essential elements that play an important role in the initiation of transcription and replication (Wolstenholme, 1992;Zhang et al, 1995;da Silva et al, 2009).…”
Section: Introductionmentioning
confidence: 99%